The The Implementation Of Information Disclosure Through Monitoring And Evaluation In Regional Organizations At Banten Province - Lutfi, Lutfi; Hilman, Hilman; Sonjaya, Trisna (Sean Institute, 2024)
The implementation of information disclosure in public bodies is an order in law number 14 of 2008 concerning openness of public information which applies to all public bodies, both in the central government through ministries and other state institutions and regional governments through regional organizations or regional work units. The importance of monitoring and evaluating the implementation of this law for regional officials in order to ensure that public information services are periodic, at any time, immediately, and information that is excluded can run well. Research data was taken from the results of monitoring and evaluation activities in 2023 by the Banten Information Commission on 39 regional apparatus organizations. Through a qualitative approach, the data is processed and described according to data from indicators I, II, III and IV, namely website development, public information development, public information services and public information provision. The monitoring and evaluation results show that of the 39 public bodies, 25 public bodies are informative, 9 are informative, 2 are quite informative, and 3 are less informative. This confirms that the majority of regional apparatus organizations are informative by implementing public information service standards that refer to PERKI 1 of 2021. However, in the future, information and documentation management officials in regional apparatus organizations still need to maximize services for public information requests for applicants and information users. whose numbers continue to increase. So, the quantity and quality of monitoring and evaluation of public bodies needs to be continuously maintained by the information commission.